Hermeneutika Hadis Sa’dudin Al-Utsmani: Studi Kitab Al-Manhaj Al-Wasthi Fi At-Ta’amil Ma'a Al-Sunnah Al-Nabawiyyah - Mutia Mahdalena Efendi; Wely Dozan (UIN Mataram, 2020)
The term heremeneutics in contemporary thought is often used as a reference in understanding the text of the Qur'an and Hadith. Hermeneutics serves as a tool for producing understanding and the most well-known methodology for understanding texts contextually and structurally well. The focus of this research will be to map understanding significantly through the hermeneutic theory of contemporary ulama, namely Sa'dudin al-Ustmani in his book